Rainfall variability maintains grass‐forb species coexistence. (12th July 2019) - Hallett, Lauren M.; Shoemaker, Lauren G.; White, Caitlin T.; Suding, Katharine N.
Abstract: Environmental variability can structure species coexistence by enhancing niche partitioning. Modern coexistence theory highlights two fluctuation‐dependent temporal coexistence mechanisms —the storage effect and relative nonlinearity – but empirical tests are rare. Here, we experimentally test if environmental fluctuations enhance coexistence in a California annual grassland. We manipulate rainfall timing and relative densities of the grass Avena barbata and forb Erodium botrys, parameterise a demographic model, and partition coexistence mechanisms. Rainfall variability was integral to grass–forb coexistence. Variability enhanced growth rates of both species, and early‐season drought was essential for Erodium persistence. While theoretical developments have focused on the storage effect, it was not critical for coexistence. In comparison, relative nonlinearity strongly stabilised coexistence, where Erodium experienced disproportionately high growth under early‐season drought due to competitive release from Avena . Our results underscore the importance of environmental variability and suggest that relative nonlinearity is a critical if underappreciated coexistence mechanism.